2013
DOI: 10.2527/jas.2012-5977
|View full text |Cite
|
Sign up to set email alerts
|

Use of residual feed intake in Holsteins during early lactation shows potential to improve feed efficiency through genetic selection1

Abstract: Improved feed efficiency is a primary goal in dairy production to reduce feed costs and negative impacts of production on the environment. Estimates for efficiency of feed conversion to milk production based on residual feed intake (RFI) in dairy cattle are limited, primarily due to a lack of individual feed intake measurements for lactating cows. Feed intake was measured in Holstein cows during the first 90 d of lactation to estimate the heritability and repeatability of RFI, minimum test duration for evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
96
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 33 publications
15
96
3
Order By: Relevance
“…This difference could be due to the length of the study period (105 v. 301 days), since a range of 0.12 to 0.63 was reported in the literature for feed efficiency traits (FCR and GEE) depending on the stage of lactation (Parke et al, 1999). Estimated heritability for RFI over 301 days (0.20 ± 0.03) was similar (0.21) to that reported by Van Arendonk et al (1991) for the first 105 days of lactation, but it was different from the result of Connor et al (2013) at 0.36 during 90 days of early lactation, Vallimont et al (2011) at 0.07 over 305 days of lactation, and pooled estimates of 0.04 reported by Berry and Crowley (2013). The discrepancies between our results with those of Vallimont et al (2011) may be due to frequency of feed intake data where our study measured daily feed intake data on each animal over 301 days and LDMI = lactation dry matter intake over 301 days (kg); LAEI = lactation actual energy intake over 301 days (Mcal /kg); ABW = average BW over 301 days (kg); ABCS = average body condition score over 301 days; LFCM = lactation fat corrected milk over 301 days (kg); LECM = lactation energy corrected milk over 301 days (kg): LFCR = lactation feed conversion ratio over 301 days: LDMI/LFCM; LGEE = lactation gross energy efficiency over 301 days: LECM/LAEI; RFI = average residual feed intake over 301 days (Mcal/day); SD = standard deviation.…”
Section: Heritabilitiessupporting
confidence: 64%
See 1 more Smart Citation
“…This difference could be due to the length of the study period (105 v. 301 days), since a range of 0.12 to 0.63 was reported in the literature for feed efficiency traits (FCR and GEE) depending on the stage of lactation (Parke et al, 1999). Estimated heritability for RFI over 301 days (0.20 ± 0.03) was similar (0.21) to that reported by Van Arendonk et al (1991) for the first 105 days of lactation, but it was different from the result of Connor et al (2013) at 0.36 during 90 days of early lactation, Vallimont et al (2011) at 0.07 over 305 days of lactation, and pooled estimates of 0.04 reported by Berry and Crowley (2013). The discrepancies between our results with those of Vallimont et al (2011) may be due to frequency of feed intake data where our study measured daily feed intake data on each animal over 301 days and LDMI = lactation dry matter intake over 301 days (kg); LAEI = lactation actual energy intake over 301 days (Mcal /kg); ABW = average BW over 301 days (kg); ABCS = average body condition score over 301 days; LFCM = lactation fat corrected milk over 301 days (kg); LECM = lactation energy corrected milk over 301 days (kg): LFCR = lactation feed conversion ratio over 301 days: LDMI/LFCM; LGEE = lactation gross energy efficiency over 301 days: LECM/LAEI; RFI = average residual feed intake over 301 days (Mcal/day); SD = standard deviation.…”
Section: Heritabilitiessupporting
confidence: 64%
“…Vallimont et al (2011) have concluded that their method of feed intake measurement was not sensitive enough to capture the difference among the animals in their study. Moreover, the difference between our result with Connor et al (2013) could be due to differences in test length (90 v. 301), feed intake data collection methods (automated v. manual), BW and BCS data collection intervals (almost 2 weeks v. 4 weeks), and other management procedures. However, these results altogether suggest that feed efficiency and of particular interest RFI in dairy cattle could be improved through genetic selection.…”
Section: Heritabilitiesmentioning
confidence: 59%
“…The amounts of feed offered and refusal were measured daily, and the feed intake was calculated by difference. Connor et al (2013) defined RFI as the residuals from a regression model that regressed daily dry matter intake (DMI) on parity, metabolic BW, change in BW and energy-corrected milk yield. In the present study, each animal's RFI (kg/day) was computed using the actual feed intake (kg/day) minus the expected feed intake (EFI, kg/day).…”
Section: Methodsmentioning
confidence: 99%
“…Although few studies have estimated RFI in lactating dairy cattle, primarily due to a lack of availability of individual feed intake measurements, limited studies showed that lactating dairy cattle with low RFI also have strong competitive advantages in production (Lopez-Villalobos et al, 2008). Connor et al (2011 and2013) reported that substantial variations have been observed among cows with different RFI, including differences in DMI, feeding behaviors and fertility measures.…”
Section: Introductionmentioning
confidence: 99%
“…The topic of production efficiency, within the context of livestock production systems, has 116 received renewed attention in recent years (Spurlock et al, 2012;Berry and Crowley, 2013; 117 Connor et al, 2013). The great debate concerning land use for ruminant production versus 118 production of human edible feed is a primary driver for this renewed interest in production 119 efficiency (Wilkinson, 2011).…”
Section: Introduction 115mentioning
confidence: 99%